Question and Answers Forum

All Questions      Topic List

UNKNOWN Questions

Previous in All Question      Next in All Question      

Previous in UNKNOWN      Next in UNKNOWN      

Question Number 27281 by kemhoney78@gmail.com last updated on 04/Jan/18

∫_(−1) ^1  (x^2 +cos x) log (((2+x)/(2−x)))dx = 0

11(x2+cosx)log(2+x2x)dx=0

Commented by abdo imad last updated on 04/Jan/18

let put  f(x)= (x^2 +cosx)ln(((2+x)/(2−x)))) we have  f(−x) =(x^2 +cosx)ln(((2−x)/(2+x))) =−(x^2 +cosx)ln(((2+x)/(2−x))))  =−f(x)   f is impar⇒ ∫_(−1) ^1 f(x)dx=0

letputf(x)=(x2+cosx)ln(2+x2x))wehavef(x)=(x2+cosx)ln(2x2+x)=(x2+cosx)ln(2+x2x))=f(x)fisimpar11f(x)dx=0

Answered by ajfour last updated on 04/Jan/18

I=∫_(−1) ^(  1) (x^2 +cos x)log (((2+x)/(2−x)))dx    =∫_(−1) ^(  1) (x^2 +cos x)log (((2−x)/(2+x)))dx  using ∫_a ^(  b) f(x)dx=∫_a ^(  b) f(a+b−x)dx  2I=∫_(−1) ^(  1) (x^2 +cos x)[log (((2+x)/(2−x)))+log (((2−x)/(2+x)))]dx  2I=0  ⇒  I=0 .

I=11(x2+cosx)log(2+x2x)dx=11(x2+cosx)log(2x2+x)dxusingabf(x)dx=abf(a+bx)dx2I=11(x2+cosx)[log(2+x2x)+log(2x2+x)]dx2I=0I=0.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com